Between global collaboration and national competition: Unraveling the many faces of Arctic science diplomacy - Nicolas Rüffin; Anna-Lena Rüland (Polar Record, 2022)
It has been argued that science diplomacy (SD) helps avoid or mitigate conflicts among stakeholders in the Arctic. Yet underlying some of these well-intended and sometimes successful initiatives is a one-sided understanding of SD. The most recent literature takes a more differentiated approach towards the means and ends of SD. It shows that international scientific interaction is shaped by the twofold logic of competition and collaboration. Instruments of SD can be meant to serve national interests, collective regional goals or global agendas. The present paper disentangles these confounding discourses of collaboration and competition based on a conceptually enhanced SD framework. It analyses Arctic strategies and two cases of Arctic SD, the Agreement on Enhancing International Arctic Scientific Cooperation and research activities on Svalbard, to reveal the mechanisms of collaboration and competition in the sphere of international science in relation to security, environment and economy. By pointing out where and how science is currently being used in the Arctic, this article provides (a) a systematic overview of the state of SD in the region and (b) a tool for policy-makers and scientists to assess what impact different facets of SD have in Arctic politics.
Keywords: 320; arctic governance; science diplomacy; collaboration; competition; qualitative content analysis